Productivity in Construction and Quantity Surveying Functions: Assessing User Satisfaction with the Effectiveness of Software Design - Amadi Alolote Ibim (International Journal of Industrial and Product Design Engineering, 2025)
Information technology has had a significant impact on the productivity of business operations and processes in construction. Quantity surveyors are responsible for managing labour, time, and cost in construction projects, with the primary aim of achieving high levels of productivity. Given the transformative potential of information technology, the professional services of quantity surveyors have been digitalized to meet the demands of construction stakeholders through the development of different software packages. It has been difficult for the quantity surveying industry to embrace information and communication technology in order for enhanced professional practice and construction productivity. The ease of use in software design, rather than progress in technology, is the true challenge of the information revolution. This study assesses the effectiveness of the design of different quantity surveying software packages in boosting productivity and facilitating project efficiency in terms of user satisfaction, cost and time savings achieved through their use. The population under investigation for this study comprises quantity surveying professionals engaged in the construction industry in Port Harcourt, Nigeria. Using the survey research strategy, data was collected and analyzed using frequency analysis to determine the distribution of responses. The findings reveal that there is a relatively high level of satisfaction with quantity surveying–based software packages, given the positive impact of these tools on productivity and project-related processes. Suggestions were however made regarding improvements in software integration capabilities, awareness, and familiarity, emphasizing the need for additional training and support resources. This insight identifies specific areas where users perceive the need for enhancement within the software packages, neccesary for increased user satisfaction.
Keywords: information technology; quantity surveyors; software packages; user satisfaction